FORAGE SPECIES USED BY LÄ°VESTOCK Ä°N THE KUMBUNGU DÄ°STRICT OF THE NORTHERN REGÄ°ON, GHANA - Ziblim, A. I.; Abdul-Rasheed, S.; Aikins, T. K. (UDS International Journal of Development, 2015)
Livestock production in the Northern Region is a major activity in the livelihoods of the population and contributes greatly to income generation in the region. The annual growth rate of free ranging ruminants is limited by forage quality and quantity especially during the dry season. This study was carried out to identify the grass/forbs and browse species used to feed livestock, rank the identified grasses/forbs and browse species in order of preference by livestock and to identify the parts of the browse mostly eaten by the animals. Ten communities were randomly selected from the study area for the research. Personal observation and questionnaire administration were employed to collect the data. In all, one hundred respondents were interviewed. Twenty-seven (27) grasses/forbs and thirty-two (32) browse species were identified. Setaria pallide fusca was the most preferred grass species whiles Securinega virosa was the most preferred browse species by the livestock in the study area. The study also revealed that livestock farmers currently travel longer distances (over 4km) to harvest these species. The large number of forage species being used indicate that the study area is rich in grasses/forbs and browse species. However, there is a threat to these species due to annual bush fires. Therefore, livestock farmers should incorporate forage cultivation into their annual crop farming systems to supplement the feeding of their animals.